Preparation of polypyrrole nanocomposites for high-performance supercapacitor electrodes / John Kevin Gan Zi Yi - John, Kevin Gan Zi Yi (2016)
Electrode material is of great importance for the realization of high-performance supercapacitors. Hence, improving the electrochemical aspects of the electroactive materials will inevitably enhance the performance of supercapacitors. This work aims to harness the properties of interest of polypyrrole (PPy) through the synthesis of PPy-based nanocomposites. This research work was divided into four stages. The first study involves the synthesis and evaluation of the capacitance performance of polypyrrole/manganese oxide (PPy/MnO2) nanocomposites. PPy/MnO2 nanocomposites with compact sheet, fibrous-porous and granular morphologies were synthesized by simply tuning the pH of the solution. The optimum pH condition was found to be 4.0, producing highly porous PPy/MnO2 nanocomposite that enabled the rapid intercalation/deintercalation of the electrolyte. As a result, a specific capacitance of up to 306 F g−1 was obtained for the porous PPy/MnO2 nanocomposite. The second part of this work was to improve the electrode wettability of the PPy electrode by the integration of chitosan biopolymer. The newly obtained hydrophilic properties of the polypyrrole/chitosan (PPy/CS) nanocomposites elicited an improvement in its specific capacitance. Hence, the nanocomposite PPy/CS displayed a specific capacitance of 403 F g−1 as opposed to 273 F g−1 for the pure PPy electrode calculated at 0.2 A g−1. Contact angle measurement indicated an improvement in the hydrophilicity of PPy/CS nanocomposites. The increased surface wettability of the nanocomposite electrode effectively increased the ion-accessible surface and facilitated the electrolyte infiltration throughout the internal volume of the electrode. The third part of this work was to enhance the electronic conductivity of PPy with the incorporation of silver (Ag) particles. A hybrid silver nanoparticle/nanocluster-decorated polypyrrole demonstrated an enhanced specific capacitance of 414 F g−1. The enhanced specific capacitance was mainly attributed to the unique architecture and hybrid nanostructures of Ag. The Ag iv nanoparticles enhanced the electron hopping system of the PPy, effectively increasing the supercapacitive properties of the PPy. On the other hand, the Ag nanoclusters acted as spacers to prevent the restacking of PPy films, further extending the active sites for redox reactions, leading to improved specific capacitance. The final part of this study sought to combine the merits of the hydrophilic chitosan and highly conducting Ag with PPy. Experimental results showed that the ternary nanocomposite (Ag@PPy/CS) has a specific capacitance of 513 F g−1 at 0.2 A g−1. The improved transportation of electrolyte ions and electrons by the incorporation of chitosan and Ag led to a pronounced enhancement in the supercapacitive property of PPy.